REACTUALIZING ISLAMIC PHILOSOPHY AND RESPONDING TO THE CRISIS OF MODERN HUMANISM - Aksan, Sahjad M. (MSJ : Majority Science Journal, 2025)
The modern humanism crisis is marked by the reduction of the human being into a material, economic, or algorithmic entity, accompanied by digital fragmentation, identity instability, and the loss of spiritual orientation. This condition reveals the limitations of secular humanism in addressing the ontological and ethical needs of contemporary individuals. This study aims to examine how the re-actualization of Islamic philosophy can provide a holistic and relevant alternative to modern humanism. Employing philosophical library research with a qualitative hermeneutic approach, the study analyzes classical Islamic philosophical texts alongside contemporary literature on humanism, spirituality, and modern crises. The findings demonstrate that the Islamic philosophical conception of the human, integrating rational, spiritual, moral, and cosmological dimensions, offers a more comprehensive ontological and epistemological foundation compared to the atomistic nature of modern humanism. By synthesizing reason (‘aql), revelation, virtue ethics, and a teleological understanding of life, the proposed Islamic humanistic framework effectively responds to contemporary challenges such as existential anxiety, digital disruption, moral decline, and ecological degradation. The study concludes that re-actualizing Islamic philosophy is not a nostalgic return to the past but a constructive effort to rebuild human dignity through the integration of rationality, spirituality, and transcendental values